An Analysis of Teacher’s Activities in Teaching Speaking: (A Descriptive Research to the Eight Grade Students of SMPN 3 Sungai Kunyit in the Academic Year of 2022/2023) - Agustri, Pegi; Clarry Sada; Eni Rosnija; Endang Susilawati; Sumarni (Kirana Publisher (KNPub), 2023)
This research aims to determine the activities that are used by teacher in teaching speaking. The subject of this research is an English teacher of SMP N 3 Sungai Kunyit. This research used a descriptive qualitative design, and data were collected from observations and interview. The findings showed that there were four activities that are used by the teacher in teaching speaking. The first activity was drilling. The second activity was running dictation. The third activity was discussion. The fourth activity was dialogue. The activity was used by the teacher because it is based on a guidebook and is simple to implement. Other activities are occasionally employed by the teacher, but are rarely because they are unappropriated for the teaching and learning process in the classroom.